KAJIAN TEORI DAN PRAKTIK INTERVENSI PEKERJA SOSIAL DALAM MELAKUKAN DUKUNGAN PSIKOSOSIAL KEPADA KORBAN KEKERASAN SEKSUAL - Ahmad Zaky; Yulianti Yulianti (Social Welfare Study Program, 2022)
Abstract. Sexual violence that occurs in Indonesia is increasingly prevalent and the victims of sexual violence are women. Sexual violence also occurs in educational institutions such as universities. The phenomenon of sexual violence in college can occur due to several factors and can be done by anyone if any opportunity. Sexual violence experienced by women resulting in prolonged trauma and requires social and psychological assistance to heal their trauma. This study aims to see how social worker interventions to carry out psychosocial support to victims of female sexual violence. The research method uses descriptive qualitative research to be able to explain the research results comprehensively. Data collection techniques using observation, interviews and documentation studies. Interviews were conducted with the academy and social worker profession at LK3 UIN Syarif Hidayatullah Jakarta. The results showed that sexual violence to students who had received assistance from LK3 UIN Syarif Hidayatullah Jakarta was caused by several factors, namely factors of proximity, attachment, and helplessness, as for the services of social workers LK3 UIN Syarif Hidayatullah Jakarta based on knowledge, skills and values and ethics applied in social worker practices. In this study, it was found that the theory used by social workers at LK3 UIN Syarif Hidayatullah Jakarta used Strength Based Perspective. The stages of services carried out by social workers at LK3 UIN Syarif Hidayatullah Jakarta to clients of victims of sexual violence are relationship building, assessment (problem digging), intervention planning (planning), implementation of interventions, evaluation, termination and follow-up.Keywords: Sexual Violence, Intervention, Social Worker. Abstrak. Kekerasan seksual yang terjadi di Indonesia semakin marak dan korbannya adalah perempuan. Kekerasan seksual juga terjadi di lembaga pendidikan seperti perguruan tinggi. Fenomena kekerasan seksual di perguruan tinggi bisa terjadi karena beberapa faktor dan bisa dilakukan oleh siapa pun. Kekerasan seksual yang dialami oleh perempuan berakibat trauma berkepanjangan dan membutuhkan pendampingan sosial dan psikologi untuk menyembuhkan traumanya. Penelitian ini bertujuan melihat bagaimana intervensi pekerja sosial melakukan dukungan psikososial kepada korban kekerasan seksual perempuan. Metode penelitian menggunakan penelitian kualitatif deskriptif untuk dapat menjelaskan hasil penelitian secara komprehensif. Teknik pengumpulan data dengan menggunakan observasi, wawancara dan studi dokumentasi. Wawancara dilakukan kepada akademi dan profesi pekerja sosial di LK3 UIN Syarif Hidayatullah Jakarta. Hasil penelitian menunjukan bahwa kekerasan seksual pada mahasiswa yang sudah mendapatkan pendampingan dari LK3 UIN Syarif Hidayatullah Jakarta disebabkan oleh beberapa faktor yaitu faktor kedekatan, kelekatan, dan ketidakberdayaan, Adapun pelayanan pekerja sosial LK3 UIN Syarif Hidayatullah Jakarta berdasarkan pengetahuan, keterampilan serta nilai dan etika yang diterapkan dalam praktik pekerja sosial. Dalam penelitian ini, teori yang digunakan oleh pekerja sosial di LK3 UIN Syarif Hidayatullah Jakarta adalah Strength Based Perspektif. Adapun tahapan pelayanan yang dilakukan oleh pekerja sosial di LK3 UIN Syarif Hidayatullah Jakarta kepada klien korban kekerasan seksual yaitu, penjalinan relasi, assesment (penggalian masalah), perencanaan intervensi(planning), pelaksanaan intervensi, evaluasi, terminasi dan follow-up.Kata kunci: Kekerasan Seksual, Intervensi, Pekerja Sosial.